The Virtue of Wudhu from the Perspective of Hadith Keutamaan Berwudhu’ dari Perspektif Hadis - Muhd. Ridwan; Dadah Dadah (Gunung Djati Conference Series, 2021)
This study aims to discuss the virtues of ablution from a hadith perspective. This research is a qualitative type by applying literature study. The research was carried out by collecting literary sources, both primary and secondary. The results and discussion of this study include the definition of ablution ', hadiths about the procedures for ablution, and the virtues of ablution' from the perspective of hadith. The conclusion of this research is that ablution 'is an activity of washing the limbs that have been determined from the face to the feet in sequence, and there are also virtues of ablution' from the perspective of hadith, including the elimination of mistakes and elevation, the removal of sins that have been committed. in every limb until the last drop of water, and the angel will pray for someone who stays the night or sleeps in a holy state to have his sins washed away.